Distribution of Personal Protective Equipment to Health Workers in The Context of Handling The COVID-19 Pandemic in Bandung - Ragil Pardiyono; Gianti Puspawardhani; Hermita Dyah Puspita; Oviyan Patra; Nurhadi Nurhadi; Rinto Yusriski; Adi Ganda Putra (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
This community service distribution of personal protective equipment (PPE) is carried out to ease the burden on doctors and health workers in the fight against the Covid-19 pandemic. The success of this service is measured by the distribution of personal protective equipment for doctors and health workers. A total of 499 personal protective equipment was distributed to Dustira Cimahi Hospital, Hasan Sadikin Hospital Bandung, Muhammadiyah Hospital Bandung, Pindad Hospital Bandung, Kiara Condong Health Center Bandung and Sukapura Health Center Bandung. The evaluation of this activity is that it is necessary to carry out a similar service program to help communities affected by the pandemic